2019
DOI: 10.1021/acs.chemmater.9b03426
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Origin of Luminescence Center in 0D Cs4PbBr6 Perovskite

Abstract: Zero dimensional perovskite Cs4PbBr6 has attracted considerable attention recently not only because of its highly efficient green photoluminescence (PL), but also its two highly debated opposing mechanisms of the luminescence: embedded CsPbBr3 nanocrystals versus intrinsic Br vacancy states. After a brief discussion on the root cause of the controversy, we provide sensitive but noninvasive methods that can not only directly correlate luminescence with the underlying structure, but also distinguish point defect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
125
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(141 citation statements)
references
References 61 publications
(191 reference statements)
13
125
0
Order By: Relevance
“…We synthesized cesium lead bromide and lead bromide species using a modified version of the method reported by Imran et al 40 By varying reagent concentrations, we observed formation of nine species that could be differentiated based on their UV-Vis absorption spectra, and made reference samples to characterize and confirm their identity by UV-Vis absorption, Xray diffraction and transmission electron microscopy (TEM) ( Figure 1). CsPbBr 3 nanocubes, 22 nanoplatelets between 1 and 4 lead bromide layers 23,46 and Cs4PbBr6 17 have been thoroughly described elsewhere and our results match literature properties. We will describe the properties of CsPb 2Br5, PbBr2 nanocrystals and molecular lead halide species here in more detail, as we have found ambiguities in the literature regarding their characteristics.…”
Section: Resultssupporting
confidence: 79%
“…We synthesized cesium lead bromide and lead bromide species using a modified version of the method reported by Imran et al 40 By varying reagent concentrations, we observed formation of nine species that could be differentiated based on their UV-Vis absorption spectra, and made reference samples to characterize and confirm their identity by UV-Vis absorption, Xray diffraction and transmission electron microscopy (TEM) ( Figure 1). CsPbBr 3 nanocubes, 22 nanoplatelets between 1 and 4 lead bromide layers 23,46 and Cs4PbBr6 17 have been thoroughly described elsewhere and our results match literature properties. We will describe the properties of CsPb 2Br5, PbBr2 nanocrystals and molecular lead halide species here in more detail, as we have found ambiguities in the literature regarding their characteristics.…”
Section: Resultssupporting
confidence: 79%
“…We synthesized cesium lead bromide and lead bromide species using a modified version of the method reported by Imran et al 40 By varying reagent concentrations, we observed formation of nine species that could be differentiated based on their UV-Vis absorption spectra, and made reference samples to characterize and confirm their identity by UV-Vis absorption, Xray diffraction and transmission electron microscopy (TEM) ( Figure 1). CsPbBr 3 nanocubes, 22 nanoplatelets between 1 and 4 lead bromide layers 23,46 and Cs4PbBr6 17 have been thoroughly described elsewhere and our results match literature properties. We will describe the properties of CsPb 2Br5, PbBr2 nanocrystals and molecular lead halide species here in more detail, as we have found ambiguities in the literature regarding their characteristics.…”
Section: Resultssupporting
confidence: 82%
“…45 While we observe photoluminescence from these species ( Figure S 2.1 B), it is similar to that of CsPbBr 3 species and could easily arise due to small impurities of perovskite cubes or plates in the sample, as has been indicated for the Cs 4PbBr6 phase. 46 PbBr 2 nanocrystals, as determined by XRD (Figure 1 C2), have a variable absorption onset, occurring between 345 and 370 nm with peaks or shoulders between 330 and 350 nm (Figure 1 B2). This is close to the reflectance spectrum observed for PbBr 2 in bulk, 47 and would suggest that nanocrystals observed (Figure 1 A2) do not display strong quantum or dielectric confinement, unlike smaller structures others have prepared.…”
Section: Resultsmentioning
confidence: 99%